Development of an Active Training Method for Belt Conveyor - Szurgacz, Dawid; Zhironkin, Sergey; Pokorný, Jiří; Spearing, A J S Sam; Vöth, Stefan; Cehlár, Michal; Kowalewska, Izabela (International journal of environmental research and public health, 2021)
The global situation related to the COVID-19 pandemic has forced employers to find an adequate way to conduct training in order to ensure work safety. The underground mining industry is one of the industries which, due to its nature, was not able to switch to remote work. Conducting traditional training risked spreading the virus among workers. For this purpose, it was necessary to start a search for a form of training that would be safe and would not cause additional stress for employees. Research on the development of an active employee training method and testing of the method itself was conducted online. In order to develop a method of active training, one of the most important workstations was selected, which is the operation of the conveyor belt. The training method comprises four training modules. The modules cover questions related to the operation of the conveyor belt, emergencies, its assembly and disassembly, repair and maintenance. The developed issues also take into account questions concerning natural hazards and work safety. The entire training course lasts 10 days. Every day, an employee receives a set of eight questions sent to their email address, which they must answer before starting work. The article describes the methodology and implementation of the training.
Keywords: active training method; COVID-19; Pandemics; Humans; work safety; occupational stress; pandemie; underground mining; human factor; lidé; SARS-CoV-2